Effects of aquatic exercise on the improvement of lower-extremity motor function and quality of life in patients with Parkinson’s disease: A meta-analysis - Dai, Shengyu; Yuan, Haoteng; Wang, Jiahui; Yang, Yuhang; Wen, Shilin (Frontiers in Physiology, 2023)
Objective: To systematically evaluate the effect of aquatic exercise interventions on the improvement of lower-extremity motor function and quality of life in patients with Parkinson’s disease. Methods: Two researchers independently searched the literature using the PubMed, Web of Science, Embase, and Cochrane Library databases. The search period was from the establishment of the database to December 2021. The subject heading search included “hydrotherapy,” “hydro therapies,” “hydro therapeutics,” “water therapy,” “aquatic exercise therapy,” “aquatic therapy,” “water-based exercise,” “Parkinson,” “Parkinson disease,” “Parkinson’s disease,” “Parkinson’s syndrome,” “primary Parkinsonism,” “paralysis agitans,” and “randomized controlled trial (RCT).” Result: A total of 698 articles were retrieved from the four databases by searching for subject headings, and 10 RCT articles were finally included. The balance ability of aquatic exercise in patients with Parkinson’s disease (weighted mean differences [WMD] = 2.234, 95% CI: 1.112–3.357, Z = 3.9, P < 0.01), walking ability (WMD = -0.911, 95% CI: -1.581 to -0.241, Z = 2.67, P < 0.01), and quality of life (WMD = -5.057, 95% CI: -9.610 to -0.504, Z = 2.18, P = 0.029) were improved, but there was no significant difference in motor function (WMD = -0.328, 95% CI: -1.781 to 1.125, Z = 0.44, P = 0.658). Conclusion: Compared with conventional rehabilitation therapy, aquatic exercise can effectively improve balance, walking ability, and quality of life in patients with Parkinson’s disease. However, it had no obvious effect on improving motor function. This study was limited by the number and quality of the included studies, and more high-quality studies are needed to verify this.